Cryolipolysis on More than One Body Area Increases Lipid Peroxidation without Changing Lipid Profile and Inflammatory Markers - Antônio Daniel Saraiva da Costa; Amanda Suellenn da Silva Santos Oliveira; Ana Karolinne da Silva Brito; Lays Arnaud Rosal Lopes; Maísa Guimarães Silva Primo; Ana Lina de Carvalho Cunha Sales; Marcos Antônio Pereira dos Santos; Nara Vanessa dos Anjos Barros; Oséas Florêncio de Moura-Filho; Jaynara Keylla Moreira da Silva; Edwiges Ita de Miranda Moura; Massimo Lucarini; et al. (Biology, 2022)
In the present study, the effects of cryolipolysis on one and multiple body areas, assessing body composition, lipid profile and peroxidation and inflammatory markers were investigated. Twenty-four women aged between 20 and 59 years were randomly assigned to three groups: (1) control, (2) cryolipolysis on the abdomen and (3) cryolipolysis on the abdomen + flanks. Anthropometric measurements, bioimpedance and ultrasound were performed, as well serum lipid profile, lipid peroxidation markers (malondialdehyde and myeloperoxidase) and inflammatory markers (C-reactive protein and Interleukin-1β) were determined. In addition, food consumption and physical activity level were evaluated. Data were obtained at 0, 10 and 30 days (t0, t10 and t30) after cryolipolysis. Cryolipolysis did not change anthropometric measurements, body composition or lipid profile. Interestingly, the abdomen + flanks group had significantly increased plasma myeloperoxidase activity at t0, t10 and t30, and increased malondialdehyde levels at t0 and t10 when compared to the other groups. Furthermore, there were no differences between macronutrient intake and total energy value, physical activity level, malondialdehyde and interleukin-1β at t30. Cryolipolysis did not change body composition, lipid profile or inflammatory markers investigated. On the other hand, when used on the abdomen and flanks, it produced an increase in lipid peroxidation markers, malondialdehyde and myeloperoxidase.